Network pharmacology approach and experimental verification of Dan-Shen Decoction in the treatment of ischemic heart disease - Difei Gong; Tianyi Yuan; Ranran Wang; Shuchan Sun; Awaguli Dawuti; Shoubao Wang; Guanhua Du; Lianhua Fang (Taylor & Francis Group, 2023)
AbstractContext Dan-Shen Decoction, which is composed of Danshen, Tanxiang and Sharen, has a good therapeutic effect on ischemic heart disease (IHD). However, systematic research on the exact mechanism of action of Dan-Shen Decoction is still lacking. The anti-IHD effect of Dan-Shen Decoction was examined in this study using a systematic pharmacological method.Objective This study validates the efficacy and explores the potential mechanisms of Dan-Shen Decoction in treating IHD by integrating network pharmacology analyses and experimental verification.Materials and methods The active components, critical targets and potential mechanisms of Dan-Shen Decoction against IHD were predicted by network pharmacology and molecule docking. H9c2 cells were pretreated with various 1 µg/mL Dan-Shen Decoction for 2 h before induction with 1000 µmol/L CoCl2 for 24 h. The cell viability was detected by CCK8, and protein expression was detected by western blots.Results The network pharmacology approach successfully identified 69 active components in Dan-Shen Decoction, and 122 potential targets involved in the treatment of IHD. The in vitro experiments indicate that the anti-IHD effect of Dan-Shen Decoction may be closely associated with targets such as AKT1 and MAPK1, as well as biological processes such as cell proliferation, inflammatory response, and metabolism.Conclusions This study not only provides new insights into the mechanism of Dan-Shen Decoction against IHD, but also provides important information and new research ideas for the discovery of anti-IHD compounds from traditional Chinese medicine.